Transplant in acute alcoholic hepatitis: a relative contraindication. Issue 2 (14th April 2022) - Jakhete, Neha; Abutaleb, Ameer; Shetty, Kirti
Abstract : Purpose of review: The aim of this review is to provide a critical analysis of liver transplantation for alcoholic hepatitis, with an emphasis on barriers to long-term success in current implementation strategies across the United States. Recent findings: Alcohol-associated liver disease is the most rapidly increasing indication for liver transplantation in the USA. Its most severe form, acute alcoholic hepatitis, has a rising incidence particularly in the young, and is associated with a high mortality risk. Although excellent outcomes following liver transplantation for alcoholic hepatitis can be achieved, several barriers limit its routine use. These constraints include risk of allograft dysfunction, the recognition of alcohol use disorder as a multisystem disease and ethical considerations. Summary: Although liver transplantation is an important option in a carefully selected group of candidates, it should not be considered the standard of care in this condition. Consistency, transparency and consensus are necessary to formulate and implement policy changes at the national level. Following liver transplantation, wraparound services are important for relapse prevention, and to ensure long-term success and survival in this challenging group of patients.